Prerequisites of Partnership in Malaysia: Pre-Views and Post-Views - Saxena, I.C. (Journal of Malaysian and Comparative Law, 2018)
Partnership as a mode of conductig business antedates the more modern joint ventures carried on through the limited liability companies. To too many businessmen who start business often of a small nature, choose partners of mutual confidence, believe in the freedom of contract and prefer to avoid all forms of state regulation or control, the partnership style of business is still the main attraction. This article is intended to probe into the history of partnership law in the various states and straits settlement and to examine the appropriateness of the current definition of partnership as contained in section 3(1) of the Partnership Act, 1961 (revised 1974, Act 135) in retrospect and prospect. The nature of the problems relative to the definition which have come before the courts will also be reviewed. This necessarily involves comparison with the previous definitions of partnerships in the different Malay states, as well as in Sabah (then North Borneo) and Sarawak. The first traces of the statutory form of the common law of partnership in some of the Malay states are found in an enactment, to be noted below, towards the end of the nineneeth century.